2019
DOI: 10.1021/acs.jafc.9b03173
|View full text |Cite
|
Sign up to set email alerts
|

Chenodeoxycholic Acid (CDCA) Protects against the Lipopolysaccharide-Induced Impairment of the Intestinal Epithelial Barrier Function via the FXR-MLCK Pathway

Abstract: Chenodeoxycholic acid (CDCA), a primary bile acid, has been demonstrated to play important roles as a signaling molecule in various physiology functions. However, the role of CDCA in regulating intestinal barrier function remains largely unknown. This study aimed to investigate the effects of CDCA on the lipopolysaccharide (LPS)-impaired intestinal epithelial barrier function and explore the underlying mechanisms. In IPEC-J2 cells, CDCA reversed the LPS-induced increase in transepithelial electrical resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…At present, reports about the direct relationship between CDCA and EMS are not available, but many studies show that CDCA is closely related to gut microbiota and contributes to promoting intestinal homeostasis. CDCA blocks lipopolysaccharide (LPS)‐induced activation of the myosin light chain kinase (MLCK) pathway in an FXR‐dependent manner, thereby protecting the intestinal epithelial barrier function 27,28 . Animal studies have shown that UDCA can stimulate the migration of intestinal epithelial cells and protect the intestinal barrier through EGFR and COX‐2‐dependent mechanisms, 29 thus alleviating the inflammatory response and reducing the levels of TNF‐α, IL‐1β, and IL‐6 30 .…”
Section: Discussionmentioning
confidence: 99%
“…At present, reports about the direct relationship between CDCA and EMS are not available, but many studies show that CDCA is closely related to gut microbiota and contributes to promoting intestinal homeostasis. CDCA blocks lipopolysaccharide (LPS)‐induced activation of the myosin light chain kinase (MLCK) pathway in an FXR‐dependent manner, thereby protecting the intestinal epithelial barrier function 27,28 . Animal studies have shown that UDCA can stimulate the migration of intestinal epithelial cells and protect the intestinal barrier through EGFR and COX‐2‐dependent mechanisms, 29 thus alleviating the inflammatory response and reducing the levels of TNF‐α, IL‐1β, and IL‐6 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Cholestasis has been reported to decrease membrane resistance in the small intestine, decrease claudin‐1 and occludin expression, enhance mucosal permeability, and improve permeability by the administration of an agonist of farnesoid X receptor (FXR), which is a nuclear receptor for bile acids (Verbeke et al, ). Exposure of the apical membrane of epithelial cells to bile acids has been reported to restore the reduced expression of claudin‐1, ZO‐1, and occludin via the FXR‐MLCK pathway (Song et al, ). Therefore, reduced FXR activation was suggested to be involved in the down‐regulation of tight junction proteins and the increase of permeability.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of metabolites, alpha-linoleic acid (ALA), chenodeoxycholic (CDCA), ursodeoxycholic acid (UDCA) and 12,11, contributed most to differences in fecal metabolome. Ni et al (2020) suggest that CDCA, UDCA, and ALA have a protective role in the intestinal wall because of their anti-inflammatory effects (Paula et al 2018, Ko et al 2019, Song et al 2019, while 12,13-EOTrE may be related to inflammation and serve as a potential biomarker of endometriosis. Despite such findings, further studies are necessary to understand the correlation between endometriosis and these compounds (Ni et al 2020).…”
Section: Metabolomics and Endometriosismentioning
confidence: 99%